Function Public Relations Management (HUMAS) in Islamic Education Institutions - Madyan, Madyan; Musli, Musli; Dika Kurniawan , Trio; Musriah, Musriah; Farida, Farida; Ainul Yakin, Muhammad; Jafar, Hasimi (Mudir : Jurnal Manajemen Pendidikan, 2023)
School and community relations are important pillars in advancing the institution. Therefore, good management is needed in its management, so that a harmonious relationship is formed between the institution and the community. This paper aims to describe the function of public relations management (HUMAS) in Islamic educational institutions which includes planning, organizing, implementing and evaluating. The method used in this research is literature study where research utilizes library sources in obtaining research data. Data collection begins with a review of books, literature studies, notes, and reports that have a relationship with public relations management at Islamic educational institutions. The results of this paper indicate that Islamic educational institutions are currently implementing public relations management (HUMAS) but have not implemented it optimally. This can be seen from the various studies that have been carried out by researchers with the results of their research that many Islamic educational institutions do not function public relations management (HUMAS) so that it has a negative impact on institutions, which makes institutional and community relations not good and in the end the public's trust is lost. against institutions.